1960
DOI: 10.1017/s0031182000025464
|View full text |Cite
|
Sign up to set email alerts
|

New species and new records of Argasidae from Israel. Observations on the rudimentary scutum and the respiratory system of the larvae of the Argasidae

Abstract: 1. The dorsal plate which probably represents a rudimentary scutum in some Argasid larvae is discussed and described.2. The respiratory system of the larvae of some species of Argas and Ornithodorus is described.3. The systematic position of the lahorensis group of the genus Ornithodorus is discussed and the use of the name Alveonasus with an emended diagnosis for this group is suggested.4. Ornithodorus procaviae n.sp. is described. Two other probably new species are described provisionally, but not named.5. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…These larvae differed in a number of ways from A.reflexus , and were preliminarily attributed to A.hermanni . However, after examining some A. hermanni larvae from Egypt, Theodor & Costa (1960) found several differences from the larvae collected in Israel concerning the number of rows of hypostomal teeth, the palp formula and the shape of the cheliceral teeth. Our retrospective analysis of the description and examination of the figure in their paper ( Theodor & Costa 1960, pp.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…These larvae differed in a number of ways from A.reflexus , and were preliminarily attributed to A.hermanni . However, after examining some A. hermanni larvae from Egypt, Theodor & Costa (1960) found several differences from the larvae collected in Israel concerning the number of rows of hypostomal teeth, the palp formula and the shape of the cheliceral teeth. Our retrospective analysis of the description and examination of the figure in their paper ( Theodor & Costa 1960, pp.…”
mentioning
confidence: 91%
“…Theodor & Costa (1960, 1967) also found a number of Argas larvae, mainly on Corvus rhipidurus , the fan‐tailed raven, in the Negev (30–31°N, 35°E) and more rarely on Coracias garrulus , the roller, and Streptopelia turtur , the turtle dove (localities of the latter species were not indicated). These larvae differed in a number of ways from A.reflexus , and were preliminarily attributed to A.hermanni .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Beament (1959) has suggested that sealing the spiracles of living specimens with wax may minimize these effects, but resultant CTT transitions may actually represent phase changes in the sealer itself. Rather, tick larvae are ideal for investigating CTTs because this developmental stage lacks spiracles and organized respiratory and tracheal systems (Theodor and Costa, 1960;Kntille, 1966;Kniille and Devine, 1972). As such, they can be studied alive.…”
Section: Introductionmentioning
confidence: 99%